1984
DOI: 10.1080/07435808409036509
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum High Density Lipoproteins in Adrenal Steroidogenesis

Abstract: The rat adrenal cortex possesses at least two mechanisms for uptake of extracellular lipoprotein cholesterol; one is receptor mediated endocytosis and the second is a non-endocytotic pathway. The latter was revealed by the ability of lipoproteins such as HDL which do not possess apo B or apo E to enhance steroid hormone output. Rat adrenocortical cell uptake of HDL cholesterol is saturable and differs for unesterified cholesterol and cholesterol esters. In addition rat adrenocortical cells possess ACTH regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…In addition, expression of the LDL receptor (LDLR) has also been detected on glucocorticoid-producing cells of the adrenal zona fasciculata (Fong et al 1989). In line with this, in vitro studies have suggested that both HDL and LDL fractions are capable of supplying cholesterol to the steroidogenic pool of cultured adrenocortical cells (Gwynne & Hess 1980, Higashijima et al 1987, Rainey et al 1992, Yaguchi et al 1998.…”
Section: Introductionmentioning
confidence: 76%
“…In addition, expression of the LDL receptor (LDLR) has also been detected on glucocorticoid-producing cells of the adrenal zona fasciculata (Fong et al 1989). In line with this, in vitro studies have suggested that both HDL and LDL fractions are capable of supplying cholesterol to the steroidogenic pool of cultured adrenocortical cells (Gwynne & Hess 1980, Higashijima et al 1987, Rainey et al 1992, Yaguchi et al 1998.…”
Section: Introductionmentioning
confidence: 76%
“…The influence of lipoproteins on steroidogenesis has also been investigated by previous workers, although the majority of studies have been performed from a non-endocrinological perspective with the primary interest being directed towards the biochemistry of cholesterol per se and its subsequent uptake and metabolism, rather than the modulation of glucocorticoid secretion and synthesis. These studies on lipoprotein metabolism have revealed that LDL-cholesterol is preferentially utilised in mice (Faust et al 1977) and human fetal cells , Carr et al 1980, Higashijima et al 1987, whilst HDL-cholesterol is the preferred substrate in rats (Gwynne et al 1976, Andersen & Dietschy 1978, Gwynne & Hess 1980. Studies using bovine adrenocortical cells have demonstrated variable results and few have directly compared the relative effects of HDL and LDL, although preincubation with either lipoprotein increased both basal and ACTH-stimulated steroidogenesis (Koper et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…HDL CE selective uptake is defined as the movement of CE from HDL into target cells without significant internalization and degradation of the HDL particle (Gwynne and Hess, 1980;Glass et al, 1983;Stein et al, 1983;Reaven et al, 1984;Glass et al, 1985;Pittman et al, 1987). This mechanism is distinct from that of the LDL receptor pathway, where LDL is internalized and the particle is degraded in the endosomal/lysosomal pathway (Brown and Goldstein, 1986).…”
Section: Introductionmentioning
confidence: 99%